The Effect of Local Wisdom on Maternal and Child Health - Ana Do Rosário De Jesus Leite; Joaquim Pinto; Carlos Boavida Tilman; Antonio Ximenes (West Science Interdisciplinary Studies, 2025)
Maternal and child health remains a major public health concern, where health outcomes are shaped not only by medical and socioeconomic factors but also by sociocultural contexts. This study aims to examine the effect of local wisdom on maternal and child health using a quantitative approach. A total of 150 respondents were surveyed using a structured questionnaire measured on a five-point Likert scale. The data were analyzed using SPSS version 25, including descriptive statistics, validity and reliability tests, and simple linear regression analysis. The results indicate that local wisdom has a positive and statistically significant effect on maternal and child health (β = 0.683, p < 0.001). The coefficient of determination (R² = 0.386) shows that local wisdom explains 38.6% of the variation in maternal and child health outcomes. These findings suggest that culturally embedded values, beliefs, and community practices play an important role in shaping maternal and child health behaviors. Integrating local wisdom into maternal and child health programs can enhance community acceptance, strengthen preventive care, and improve health outcomes. This study provides empirical evidence supporting the inclusion of cultural dimensions in the formulation of maternal and child health policies.⁠